2014
DOI: 10.1111/vec.12123
|View full text |Cite
|
Sign up to set email alerts
|

Bispectral index analysis during cardiac arrest and cardiopulmonary resuscitation in a propofol‐anesthetized calf

Abstract: This is the first report in which BIS is documented together with standard monitoring techniques during cardiopulmonary arrest and resuscitation in a calf. BIS varied with cardiovascular performance, and may be indicative of cerebral blood flow in this context. Further research may be warranted to define the role of BIS for monitoring cerebral activity during CPR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Interstitial dehydration has been cited as a contraindication for the administration of hypertonic saline [46]. In adult bovines, it is recommended that 20 L of fluids should be administered IV or by orogastric tube after IV hypertonic saline administration [19]. In case 1, the concerns regarding damage to the surgical site precluded orogastric tube administration of fluids post-operatively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interstitial dehydration has been cited as a contraindication for the administration of hypertonic saline [46]. In adult bovines, it is recommended that 20 L of fluids should be administered IV or by orogastric tube after IV hypertonic saline administration [19]. In case 1, the concerns regarding damage to the surgical site precluded orogastric tube administration of fluids post-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases atropine was used in an attempt to treat bradycardia. The expected HR for an adult bovine under general anaesthesia is 60-90 bpm [19]. Heart rate for 2 month old calves under general anaesthesia has not been reported, however the average HR for a 55-60 days old awake calf is reported to be 98 bpm [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has precluded the validation of BIS values because the development of this index for humans, as well as for use in animals, especially in cattle, has only recently begun. Using the BIS, APREA et al (2014) clearly showed in a case report of the cardiopulmonary resuscitation of a propofol-anesthetized calf that the BIS values that were assessed had varied with cardiovascular function and that BIS was indicative of cerebral perfusion in cattle. ARAÚJO et al (2014) and reported mean BIS values of approximately 40 when conducting studies in calves using inhalation anesthesia with isoflurane combined with butorphanol infusion, and assessing BIS in isoflurane-anesthetized calves with or without CRI of lidocaine, respectively.…”
Section: Discussionmentioning
confidence: 99%